(untitled) (Revista Brasileira Multidisciplinar, 2023)
This article aims to critically and evaluatively analyze the scientific study on the relationship and confrontation of the limits of rights and constitutionally guarantee results related to procedural law and criminal material, which are: the right to silence and non-self-incrimination, with crime of perjury. It should be noted, in principle, that Brazilian legislation does not provide for the crime of perjury as a punishable practice, despite the fact that a bill for its creation has already been filed. With this in mind, it should be noted that during the processing of criminal actions under the national rules, the protection of in dubio pro reo is trained, as well as the guarantee of non-self-incrimination, the accused is not obliged, as well as the witnesses, to make a true commitment to the facts narrated, as well as he also reserves the right to silence without any prejudice. It is bibliographical research, using data through the analysis of national and international doctrines, laws and scientific articles. Thus, it sought to analyze the effective scope of the right to silence in the criminal sphere, comparing such limits as well, between the guarantee of non-self-incrimination and foreign literature on the crime of perjury.